2008
DOI: 10.1016/j.cellbi.2007.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A treatment induces apoptosis through an oxidant‐dependent activation of the mitochondrial pathway

Abstract: Even though retinoids are widely used as adjuvant in chemotherapeutic interventions to improve cancer cell death, their mechanism(s) of action involves multiple overlapping pathways that remain unclear. We have previously shown that vitamin A, the natural precursor of the retinoids, induces oxidative-dependent cytochrome c release from isolated mitochondria, suggesting a putative mechanism for apoptosis activation. Using Sertoli cells in culture, we show that retinol causes mitochondrial-dependent apoptosis, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…There is evidence to suggest that the SOD/CAT ratio plays a role in the ultimate levels of cellular oxidative stress[8] and this oxidative stress may be a precursor to other cellular effects such as apoptosis[15]. Since MnSOD generates the substrate for CAT- H 2 O 2 , an oxidant, an increase in MnSOD without a concurrent increase in CAT levels can lead to increased oxidative stress and lipid peroxidation as seen in our results.…”
Section: Discussionsupporting
confidence: 57%
“…There is evidence to suggest that the SOD/CAT ratio plays a role in the ultimate levels of cellular oxidative stress[8] and this oxidative stress may be a precursor to other cellular effects such as apoptosis[15]. Since MnSOD generates the substrate for CAT- H 2 O 2 , an oxidant, an increase in MnSOD without a concurrent increase in CAT levels can lead to increased oxidative stress and lipid peroxidation as seen in our results.…”
Section: Discussionsupporting
confidence: 57%
“…All trans retinoic acid was used by Bai et al [5] who show that retinoic acid ameliorated TNBS induced colitis probably by shifting Th1 to TH2. In an in vitro study retinols caused mitochondrial dependent apoptosis [6] .More than 90% of oxygen consumption in tissues is attributed to mitochondrial respiration. Mitochondria are pivotal organelles in controlling necrotic and apoptotic processes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, de Oliveria and colleagues concluded that structural changes within actin filaments in treated Sertoli cells enabled electrons produced via retinol metabolism to be transmitted to the mitochondria. This process, in turn, led to overloading this organelle with a supply of electrons and induced superoxide radical production, which initiated oxidative stress [102] and disturbed mitochondrial metabolism, detected via a reversible drop in mitochondrial activity and cellular adenosine triphosphate levels [103,104]. The end result of retinol-induced oxidative damage in Sertoli cells appears to be apoptosis.…”
Section: Sertoli Cells As a Model For Investigating Retinoid-regulmentioning
confidence: 98%
“…The end result of retinol-induced oxidative damage in Sertoli cells appears to be apoptosis. The classical, intrinsic mitochondrial apoptotic pathway (i.e., the release of death factors, such as cytochrome c, from the inner mitochondrial membrane to the cytosol) was initiated in Sertoli cells treated with retinol [90,103], as were single-and double-stranded DNA breaks, both of which are hallmarks of a normal apoptotic response. Taken together, these data suggest that excess levels of retinol can induce intracellular reactive oxygen species production, changes in cytoskeleton structure, mitochondrial damage, and apoptosis.…”
Section: Sertoli Cells As a Model For Investigating Retinoid-regulmentioning
confidence: 99%